Images of the Twenty-First Century. Proceedings of the Annual International Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.1989.96016
|View full text |Cite
|
Sign up to set email alerts
|

Tissue shape and deformation as a characterization of the seating interface

Abstract: A review of pressure measurements and previous studies which have utilized shape and deformation measurement for analysis of the seating interface is presented. A conceptual model is then developed which provides a rationale for using tissue shape and deformation as opposed to interface pressure as the primary parameterization of the seating interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Levine et al investigated dynamic changes in seat interface pressure using surface functional electrical stimulation (FES) of the gluteus maximus [15][16][17]. Interestingly, these results indicated that FES could change the shape of loaded buttocks and thereby significantly reduce pressure under the ITs and redistribute it over other parts of the seat interface.…”
Section: Introductionmentioning
confidence: 99%
“…Levine et al investigated dynamic changes in seat interface pressure using surface functional electrical stimulation (FES) of the gluteus maximus [15][16][17]. Interestingly, these results indicated that FES could change the shape of loaded buttocks and thereby significantly reduce pressure under the ITs and redistribute it over other parts of the seat interface.…”
Section: Introductionmentioning
confidence: 99%
“…Bogie et al [3] described an on-off ES duty cycle of 1:1 s in a 3 min period, with a 17 min interstimulation interval, approximating the frequency of weight shifting recommended for wheelchair users at risk of tissue breakdown [3,8,10]. This duty cycle has not been compared with other protocols; therefore, it is not clear whether this is the optimal ES-rest ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Future research has also revealed the possible additional effects of surface ES on reduction of muscle atrophy. Levine et al [6][7]17] and Levine and Kett [8] already showed that tissue shape changed and muscle hypertrophy occurred after muscle ES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A method to potentially prevent the recurrence of PU is activating the paralysed muscles using electrical stimulation (ES). ES has been found to markedly improve PU risk factors by improving paralysed muscle mass and local circulation of skin and muscle [6,[24][25][26][27][28][29][30]. However, randomized controlled trials (RCTs) to confirm the effect of ES on reduction of PU recurrence are lacking and the cost-effectiveness of ES in individuals with SCI is unknown.…”
Section: Electrical Stimulationmentioning
confidence: 99%